Irish regional GDP since independence - Alan De Bromhead; Sean Kenny (Queen's University Centre for Economic History (QUCEH), 2024)
This paper constructs the first estimates of Irish regional GDP over the twentieth century and traces the relative economic performance of Ireland's regions since independence. Using an array of data sources available at a county level, output in Agriculture, Industry and Services in benchmark census years is estimated. Applying a variety of alternative measures, we find a reduction in regional inequality over the period that is similar to the broader European pattern. Regional convergence over the period 1926-1991 was driven by both within-sector convergence in productivity and structural change. Our paper helps to understand the regional dimensions to Irish economic development from the birth of a newly independent state up to the eve of Ireland's growth 'miracle' in the 1990s, when the first official efforts were initiated to construct these figures. Finally, we connect our estimates to these official figures to examine GDP at the level of NUTS regions up to 2021.
Keywords: N34; N94; O18; R11; R12; 330; Regional GDP; Ireland; Economic History; Inequality; Economic Growth